2023
DOI: 10.3390/buildings13061523
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis on Effects of Soil Improvement on Pile Forces on Existing High-Rise Building

Abstract: Nowadays, seismic codes are regularly updated with new knowledge and a better understanding of the earthquake phenomenon. With these updates, existing buildings require a reevaluation of their stability and a process of reinforcement and/or retrofitting. This study investigated the effects of two types of ground improvement which use cement-mixing soil surrounding the foundation structure to reduce and redistribute forces acting on piles. This is especially important when the reevaluation of high-rise building… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Because the soil layer has been consolidated for a long time, the deformation has been stabilized. Therefore, the numerical simulation first carries out the ground stress equilibrium, simulating self-weight stress in the soil layer, which will not produce settlement due to self-weight [29]. After achieving ground stress equilibrium, the composite foundation generated a settlement at the order of 10 −9 mm.…”
Section: Geostress Balancementioning
confidence: 99%
“…Because the soil layer has been consolidated for a long time, the deformation has been stabilized. Therefore, the numerical simulation first carries out the ground stress equilibrium, simulating self-weight stress in the soil layer, which will not produce settlement due to self-weight [29]. After achieving ground stress equilibrium, the composite foundation generated a settlement at the order of 10 −9 mm.…”
Section: Geostress Balancementioning
confidence: 99%
“…It was observed that when the inclined pile inclination angle was 5 • , the deformation resistance of the inclined pile group foundation was improved, and the load distribution at the pile head was more reasonable. Tipsunavee et al [21] investigated the effects of two types of improvement methods with cement mixture in terms of reducing and redistributing the forces occurring in piles. In the study, the dynamic response of the soil-pile-structure interaction system of a highrise building under seismic load was investigated using numerical analysis.…”
Section: Introductionmentioning
confidence: 99%